Efficacy and Safety of Vorapaxar in Non–ST‐Segment Elevation Acute Coronary Syndrome Patients Undergoing Noncardiac Surgery. Issue 12 (15th December 2015) - van Diepen, Sean; Tricoci, Pierluigi; Podder, Mohua; Westerhout, Cynthia M.; Aylward, Philip E.; Held, Claes; Van de Werf, Frans; Strony, John; Wallentin, Lars; Moliterno, David J.; White, Harvey D.; Mahaffey, Kenneth W.; et al.
Abstract : Background: Perioperative antiplatelet agents potentially increase bleeding after non–ST‐segment elevation (NSTE) acute coronary syndromes (ACS). The protease‐activated receptor 1 antagonist vorapaxar reduced cardiovascular events and was associated with increased bleeding versus placebo in NSTE ACS, but its efficacy and safety in noncardiac surgery (NCS) remain unknown. We aimed to evaluate ischemic, bleeding, and long‐term outcomes of vorapaxar in NCS after NSTE ACS. Methods and Results: In the TRACER trial, 2202 (17.0%) patients underwent major or minor NCS after NSTE ACS over 1.5 years (median); continuing study treatment perioperatively was recommended. The primary ischemic end point for this analysis was cardiovascular death, myocardial infarction, stent thrombosis, or urgent revascularization within 30 days of NCS. Safety outcomes included 30‐day NCS bleeding and GUSTO moderate/severe bleeding. Overall, 1171 vorapaxar and 1031 placebo patients underwent NCS. Preoperative aspirin and thienopyridine use was 96.8% versus 97.7% ( P =0.235) and 89.1% versus 86.1% ( P =0.036) for vorapaxar versus placebo, respectively. Within 30 days of NCS, no differences were observed in the primary ischemic end point between vorapaxar and placebo groups (3.4% versus 3.9%; adjusted odds ratio 0.81, 95% CI 0.50 to 1.33, P =0.41). Similarly, no differences in NCS bleeding (3.9% versus 3.4%; adjusted odds ratio 1.41, 95% CI 0.87 to 2.31, P =0.17) or GUSTO moderate/severe bleeding (4.2% versus 3.7%; adjusted odds ratio 1.15, 95% CI, 0.72 to 1.83, P =0.55) were observed. In a 30‐day landmarked analysis, NCS patients had a higher long‐term risk of the ischemic end point (adjusted hazard ratio 1.62, 95% CI 1.33 to 1.97, P <0.001) and GUSTO moderate/severe bleeding (adjusted hazard ratio 5.63, 95% CI 3.98 to 7.97, P <0.001) versus patients who did not undergo NCS, independent of study treatment. Conclusion: NCS after NSTE ACS is common and associated with more ischemic outcomes and bleeding. Vorapaxar after NSTE ACS was not associated with increased perioperative ischemic or bleeding events in patients undergoing NCS.